Gallbladder schistosomiasis - Gabriela Del Angel-Millán; José Jukemura; Júlia Bragion Bicudo; Ricardo Jureidini; André Luís Montagnini; Vanderlei Segatelli; Thiago Costa Ribeiro; Guilherme Naccache Namur; Thiago Nogueira Costa; Lucas Cata Preta Stolzemburg; Emilio Elias Abdo; Ulysses Ribeiro Júnior; et al. (University of São Paulo, 2024)
Schistosomiasis is an infectious disease caused by parasitic flatworms of the genus Schistosoma. The species Schistosoma mansoni is associated with hepatosplenic disease. Schistosomiasis involving the gallbladder alone is highly unusual, with a few cases reported. Herein, we present the case of a woman from a region with endemic schistosomiasis who presented with a painless solid lesion and wall thickening of the gallbladder. She underwent an uneventful laparoscopic cholecystectomy. Microscopic examination of the surgical specimen revealed Schistosoma mansoni eggs associated with granulomatous reaction, leading to the diagnosis of schistosomiasis of the gallbladder, prompting subsequent treatment with praziquantel and follow-up. This case illustrates the importance of suspicion for this diagnosis in endemic areas, as it can be misdiagnosed with malignancy if not examined microscopically. Complications and treatment strategies are poorly characterized for the few cases of schistosomiasis; reporting this case can serve as a helpful reminder of a rare presentation of this disease.